몇 가지 장미꽃 품종의 기능 성분과 항산화 활성 - 최선영(Sun Young Choi); 김민영(Min Young Kim); 이윤정(Yoon Jeong Lee); 최은경(Ehn-Kyoung Choi); 김윤배(Yun-Bae Kim); 이준수(Junsoo Lee); 정헌상(Heon Sang Jeong) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2019)
본 연구는 몇 가지 식용 장미꽃 품종에 대한 새로운 식품 소재 개발의 가능성을 살펴보기 위하여 기능 성분 및 항산화 활성을 평가하였다. 총 폴리페놀 및 플라보노이드 함량은 덩굴장미가 각각 93.59 mg GAE/g 및 9.12 mg CE/g으로 높았으며, 아이스윙이 각각 62.76 mg GAE/g 및 2.72 mg CE/g으로 낮았다. ABTS와 DPPH 라디칼 소거능은 콜로라도 품종에서 각각 0.45 및 0.52 mg AAE/mg으로 높았다. 페놀산 화합물은 덩굴장미가 3.13 mg/g으로 가장 높았으며 콜로라도, 온누리, 아이스윙 순으로 낮아져 항산화 활성과 유사한 경향이었다. 색도 중 a값은 0.93~19.69 범위였으며, 덩굴장미가 가장 높은 값을 나타내었다. 안토시아닌 함량은 덩굴장미가 8.58 mg/L로 높았다. 프로안토시아니딘 함량은 콜로라도와 덩굴장미가 각각 1.82 및 2.50 mg CE/g의 값을 나타내었고 온누리와 아이스윙은 검출되지 않았다. 이상의 결과로부터 덩굴장미의 항산화 활성과 안토시아닌 함량이 높게 측정되어 관상적으로 그리고 식품소재로서의 적용이 가능하리라 판단된다. This study examined the functional components and antioxidant activities of four different rose flower (Colorado, Onnuri, platyphylla Thory, and Icewing cultivars) extracts to promote the value of edible flowers as new agricultural products. platyphylla Thory showed the highest total polyphenol and flavonoid contents 93.59 mg gallic acid equivalent (GAE)/g and 9.12 mg catechin equivalent (CE)/g, respectively and Icewing showed the lowest 62.76 mg GAE/g and 2.72 mg CE/g, respectively. The 2,2’-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) and 1,1-diphenyl-2-picrylhydrazyl radical scavenging activities were high in Colorado at 0.45 and 0.52 mg ascorbic acid equivalent/mg, respectively. The phenolic acid compounds showed the highest value of 3.13 mg/g in platyphylla Thory. The anthocyanin content was as high as 8.58 mg/L in the platyphylla Thory but was not detected in Icewing. The proanthocyanidins contents in Colorado and platyphylla Thory cultivars were 1.82 and 2.50 mg CE/g, respectively but they were not detected in Onnuri and Icewing. These results suggest that the antioxidant activity and anthocyanin content of platyphylla Thory are high and they can be applied as a food material. KCI Citation Count: 5